Localizing Sustainable Development Goals in Rural Areas: A Case Study on Rising Awareness in Pohjejer Village, East Jawa, Indonesia - Priambodo, Bayu; Ilman, Ghulam Maulana; Pertiwi, Vidya Imanuari (JPSI (Journal of Public Sector Innovations), 2024)
The Indonesian government, through the Ministry of Villages, has made innovative efforts in the form of the village SDGs program, where this program develops local potential at the village level. This article aims to describe a case study on an innovative program in building facilities in the Pohjejer village, East Jawa, Indonesia, through the village SDGs program. This research uses a qualitative approach, specifically adopting a case study methodology, allowing researchers to delve into the specific context and explore the complexity of the phenomenon being researched. Data collection for this research involved interviews and secondary data. Specifically, interviews will be conducted with key informants from the SDGs working group and the Pohjejer village government. The research results show that the Ministry has initiated an SDGs localization program by implementing various development projects involving village teams. However, the community has not yet felt the specific results of this program in real terms. The Ministry needs to address the need for a more visible impact from these initiatives. The synergy between local and national initiatives highlights the importance of coordinated efforts to ensure meaningful and real localized implications of the SDGs for society.